2019
DOI: 10.1158/1078-0432.ccr-18-0776
|View full text |Cite
|
Sign up to set email alerts
|

A Five-MicroRNA Signature Predicts Survival and Disease Control of Patients with Head and Neck Cancer Negative for HPV Infection

Abstract: The five-miRNA-signature is a strong and independent prognostic factor for disease recurrence and survival of patients with HPV-negative HNSCC.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 48 publications
2
54
1
Order By: Relevance
“…Low numbers in the former smoker category but also the lack of more accurate smoking status values may have decreased the power to reveal the reported association with smoking (79,98,99). Since we focused on known determinants of radiation response, other biomarkers were not included despite their relevance or prognostic value in HNSCC (5,6,16,(100)(101)(102)(103)(104)(105)(106). Some, such as tumor mutational burden (TMB) are prevalent in laryngeal and HPV-negative pharyngeal HNSCC (14) but require DNA sequencing data.…”
Section: Discussionmentioning
confidence: 99%
“…Low numbers in the former smoker category but also the lack of more accurate smoking status values may have decreased the power to reveal the reported association with smoking (79,98,99). Since we focused on known determinants of radiation response, other biomarkers were not included despite their relevance or prognostic value in HNSCC (5,6,16,(100)(101)(102)(103)(104)(105)(106). Some, such as tumor mutational burden (TMB) are prevalent in laryngeal and HPV-negative pharyngeal HNSCC (14) but require DNA sequencing data.…”
Section: Discussionmentioning
confidence: 99%
“…At present, lncRNAs and miRNAs are believed to play an important role in tumorigenesis and have been identified as potential prognostic markers for HNSCC. Yang et al [ 8 ] established an 8-lncRNA signature associated with the prognosis of HNSCC, and Hess et al [ 9 ] identified prognostic 5-miRNA signature to independently predict disease control and survival in HNSCC patients. However, autophagy, as a crucial mechanism in tumorigenesis and progression, has not been studied on the effect of autophagy-associated genes on the prognosis of HNSCC.…”
Section: Introductionmentioning
confidence: 99%
“…A large portion of the studies regarded mRNA signatures (33/61) , while a minor portion of the studies considered miRNA signatures (11/61) [52][53][54][55][56][57][58][59][60][61][62] and other non-coding RNA signatures (13/61) [63][64][65][66][67][68][69][70][71][72][73][74][75][76]. Only 4/61 [77][78][79][80] studies identified signatures by a high-throughput omics analysis of methylated DNA.…”
Section: Analysis Of Recent Epigenomics and Transcriptomics Datamentioning
confidence: 99%